Violências nas escolas: juventudes e maquinaria capitalista no oeste catarinense - Camillo, Eliane Juraski (2015)
This research study aims to answer that relations can be established between violence at school and the capitalist machinery and how it is perceived in the constitution of the young subjects. To this end, through qualitative methodology and the oral history method, they are interviewed twenty young high school students from three schools in two counties of western Santa Catarina, ten young people from the municipality of Xanxerê-SC and ten young people from the municipality of Xaxim, SC as well as non-structured interviews with / as managers / the schools and teaching staff and non-participant observation. The choice of the two municipalities for the production of data was determined by different HDI (Human Development Index) as a favorable quality strategy in qualitative research. In the narratives of / the young, are analyzed: a) what types of violence circulate in schools and in society researched crop; b) that school practices are experienced by / young and if they lead to empowerment and youth leadership or corroborate the violence; c) violence arising from the capitalist machinery occur in two municipalities, which are verified through the relationship of / girls with the work, with effective demand - consumption - and with the technologies. Data produced indicate the following results: a) in all the surveyed schools, circulate, to a lesser or greater extent, all kinds of violence that are teased in the theoretical framework, the practice violence, instrumental, utilitarian or predatory, the violence of domination, revenge, sadism or joy of damage and ideology; b) with respect to experienced school practices, they are meant differently by managers / as and young people. While those to overvalue as effective in combating violence and youth empowerment, the / young or ignore them or consider them to be contrary to its interests. Therefore, such practices do not corroborate for the empowerment and youth leadership and further corroborate with violence, because these / girls step into the school institution with cultural capital deficit, the need to obtain success in it. Thus, the school confirms the exclusion while ratifies violence. c) In relation to the capitalist machinery, it was concluded that the / young too soon step into the world of work, formal or informal, is under the need to help the household budget, either by virtue of Christian religious morality, which considers positive the suffering and hard work. These / girls are poorly paid and need to be exposed to unfavorable conditions often work in which workers' rights, safety and circumstances favorable to the full development of / the young are not observed. Also, due to the results, some strategies are presented to contain / reduce violence at school, given that they interfere negatively on the quality of education and therefore need to be addressed firmly by the various school actors, thus allowing that education may have interference on violence.